1189 Missed Opportunities for Prevention of Early Onset Group B Streptococcus (EOGBS) Infection in Northern Ireland. (October 2012) - Magowan, S; Lewis, J; Craig, S; Ong, G; Ashe, R
Abstract : Background and Aims: EOGBS infection is associated with high morbidity and mortality. Historically N. Ireland has had a higher incidence than other parts of the UK. The incidence can be reduced by intrapartum antibiotic prophylaxis (IAP). The RCOG (UK) 2003 guideline on prevention of EOGBS disease states that IAP should be considered in the presence of ≥2 risk factors for GBS. We sought to determine (1) the 2008–2010 incidence of EOGBS disease in N Ireland and (2) whether opportunities to give IAP were missed? Methods: Infants with positive blood or CSF cultures for EOGBS during 2008–2010, were identified by laboratory staff. Data was retrieved from maternal and neonatal charts of affected babies. Results: 35 infants had EOGBS infection. This gave an incidence of 0.47/1000 live births. (England & Wales incidence = 0.34/1000 live births). Four infants died; 3 due to EOGBS. Data was missing from 3 mothers. 10/32 mothers had 1 risk factor and 4/10 received IAP. 8/32 mothers had ≥2 risk factors; 4/8 received intrapartum antibiotics but only 1 as per the RCOG (UK) guidelines. One baby from this group died. Conclusions: Our data suggests that EOGBS infection rate remains higher than other parts of the UK. There appear to be significant missed opportunities for IAP. This may pertain to uncertainties in interpreting RCOG EOGBS prevention guidelines.